A chiral separation strategy for acidic drugs in capillary electrochromatography using both chlorinated and nonchlorinated polysaccharide‐based selectors. Issue 19 (14th August 2014) - Albals, Dima; Hendrickx, Ans; Clincke, Lies; Chankvetadze, Bezhan; Heyden, Yvan Vander; Mangelings, Debby; Chankvetadze, Bezhan
<x xml:space="preserve">Abstract</x> A generic chiral separation strategy for the analysis of acidic compounds in CEC is proposed in completion of an earlier defined strategy for nonacidic compounds. The screening step of this strategy uses a 45 mM ammonium formate (pH 2.9)/ACN (35/65, v/v) mobile phase, a temperature of 25°C, and an applied voltage of 15 kV. To update the screening step, eight chiral stationary phases, which all possessed chlorinated and nonchlorinated polysaccharide‐based chiral selectors, were evaluated using the earlier defined screening conditions. A combination of the two types of polysaccharide‐based chiral phases proved to have the highest cumulative success rate. In the updated screening step, amylose tris(3, 5‐dimethylphenylcarbamate) (ADH), cellulose tris(4‐methylbenzoate) (OJH), cellulose tris(3, 5‐dichlorophenylcarbamate) (SP5), and cellulose tris(3, 5‐dimethylphenylcarbamate) (ODRH) were included as selectors and their preferred screening sequence was determined as ADH > OJH > SP5 > ODRH. New optimization steps were also defined for SP5 by investigating the influences of different parameters on the separation outcome using an experimental design approach. After application of the updated strategy, 15 of 17 acidic pharmaceuticals were separated under screening conditions, of which 9 were baseline resolved. When the optimization steps were applied, another three compounds were baseline separated, while the total number of separations was increased by one, which brings the total number of separations to 16 of 17 with 12 baseline separated compounds. This reflects the successful performance of the updated strategy on acidic compounds.